A RARE INSTANCE OF LEVOSULPIRIDE–INDUCED GALACTORRHOEA - Rao, Raghavendra; Bhat, Rama; Patil, Navin; Bhushan, Lavanya; Avinash, A.; Kunder, Sushil Kiran (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Antipsychotics are well known to affect prolactin secretion, resulting in hyperprolactinemia and its consequent manifestations like amenorrhoea, galactorrhoea, gynaecomastia, etc. Levosulpiride is a novel antipsychotic drug with additional antidepressant, antiemetic and antidyspeptic actions. The authors report a case of levosulpiride-induced hyperprolactinemia, presenting as galactorrhoea in a female patient with dyspepsia at Kasturba Hospital, Manipal, in South India. Keywords: Hyperprolactinemia, Prolactin, Dyspepsia, Antipsychotic, Dopamine